Violence and abuse in society : understanding a global crisis - Browne Miller, Angela, 1952- (Santa Barbara, Calif. : Praeger, 2012)
"Suitable for professionals, students, and lay readers alike, this book provides an immensely informative, profoundly moving, and remarkably comprehensive look at the range and nature of violence and abuse by and of humans today"--
V. 1. Fundamentals, effects, and extremes -- v. 2. Setting, age, gender, and other key contexts -- v. 3. Psychological, ritual, sexual, and trafficking issues -- v. 4. Faces of intimate partner violence.
Includes bibliographical references and index.
Keywords: Violence -- Case studies; SOCIAL SCIENCE / General; POLITICAL SCIENCE / General